Learning Experiences through Reflection on Action in Pediatric Nursing Practice - ศรียะศักดิ์, อัจฉราวดี; เกตุอินทร์, วารุณี; ฉิ่งเล็ก, วิโรจน์; แสงอาทิตย์, สุวรรณี (Princess of Naradhiwas University Journal, 2019)
This qualitative study was conducted to identify the effective learning experiences through reflection on action in pediatric nursing practicum. A total of 89 third-year nursing students, having some practicum experience in the pediatric nursing field, participated in the study by writing their own reflective journal. Then purposive sampling was used to recruit 23 students in order to form 4 focus groups of 6-8 students. Content analysis was then used. Results showed the following. 1. At the beginning of their paediatric practicum, students often felt excited and challenged about creating trust when interacting with children and their families. 2. Science and art in nursing of the third-year nursing students was growing since the application of theoretical knowledge in classroom knowledge into pediatric nursing practice. 3. Self-confidence in both nursing techniques and nursing practice were important to embrace the full dimension of pediatric nursing. As a conclusion, students need to improve their pediatric nursing practice, as pre-practice preparation for nursing practice is an important issue. They need to do case study, and to search evidence-based nursing before going to practice in clinical setting. Thus, teachers should recognize the importance of improving students’ abilities in order to build a trust relationship with children and their families. Such abilities can be strengthened by applying communication techniques in family-center care. The variety of teaching strategies, such as scenarios, role play, writing reflection diary, and so on, can be applied to help students utilize theory or knowledge in practicum context. In addition, staff in clinical facilities should be aware of being a role model for students, so they can learn more effectively how to interact with children and their families.